Hyaluronidase of Bloodsucking Insects and Its Enhancing Effect on Leishmania Infection in Mice - Volfova, Vera; Hostomska, Jitka; Cerny, Martin; Votypka, Jan; Volf, Petr (PLOS Neglected Tropical Diseases, 2008)
Background Salivary hyaluronidases have been described in a few bloodsucking arthropods. However, very little is known about the presence of this enzyme in various bloodsucking insects and no data are available on its effect on transmitted microorganisms. Here, we studied hyaluronidase activity in thirteen bloodsucking insects belonging to four different orders. In addition, we assessed the effect of hyaluronidase coinoculation on the outcome of Leishmania major infection in BALB/c mice. Principal Findings High hyaluronidase activity was detected in several Diptera tested, namely deer fly Chrysops viduatus, blackflies Odagmia ornata and Eusimilium latipes, mosquito Culex quinquefasciatus, biting midge Culicoides kibunensis and sand fly Phlebotomus papatasi. Lower activity was detected in cat flea Ctenocephalides felis. No activity was found in kissing bug Rhodnius prolixus, mosquitoes Anopheles stephensi and Aedes aegypti, tse-tse fly Glossina fuscipes, stable fly Stomoxys calcitrans and human louse Pediculus humanus. Hyaluronidases of different insects vary substantially in their molecular weight, the structure of the molecule and the sensitivity to reducing conditions or sodium dodecyl sulphate. Hyaluronidase exacerbates skin lesions caused by Leishmania major; more severe lesions developed in mice where L. major promastigotes were coinjected with hyaluronidase. Conclusions High hyaluronidase activities seem to be essential for insects with pool-feeding mode, where they facilitate the enlargement of the feeding lesion and serve as a spreading factor for other pharmacologically active compounds present in saliva. As this enzyme is present in all Phlebotomus and Lutzomyia species studied to date, it seems to be one of the factors responsible for enhancing activity present in sand fly saliva. We propose that salivary hyaluronidase may facilitate the spread of other vector-borne microorganisms, especially those transmitted by insects with high hyaluronidase activity, namely blackflies (Simuliidae), biting midges (Ceratopogonidae) and horse flies (Tabanidae).